A mathematical correction based on weight analysis on instantaneous dry-bulb and wet-bulb temperatures tolerances specified for cooling capacity test and heat pump test. (2nd April 2016) - Zhang, Zhongbin; Huang, Hu; Li, Yinglin; Huang, Yi
Abstract : A mathematical method is presented and verified with a sample case for tightening instantaneous dry-bulb and wet-bulb temperatures tolerances (maximum permissible deviations) specified for cooling capacity test and heat pump test stipulated in currently enacted Chinese national room air conditioner standards. This method produces tightened dry-bulb and wet-bulb temperatures tolerances based on the investigation of room air conditioner performance test results; the determination of dry-bulb and wet-bulb temperatures intervals, where both cooling capacity and energy efficiency ratio reach the maximum increase gradient; and the analysis of the weight ratios of dry-bulb and wet-bulb temperatures' effect on cooling capacity and energy efficiency ratio. Comparisons between the standard uncertainties of dry-bulb and wet-bulb temperatures within tolerances with and without correction and between the combined standard uncertainties of the measured cooling capacity/energy efficiency ratio before and after correction are made in detail. The results show that room air conditioner performance tests with dry-bulb and wet-bulb temperatures change within the tightened tolerances can be noticeably improved in the confidence of measured cooling capacity and energy efficiency ratio profiling their true values, which eventually effectively helps improve the confidence in evaluating the energy efficiency grade of a room air conditioner unit.